Emergency remote teaching in process simulation using DWSIM: a case study from DIQ-UMAG, Chilean Patagonia - Navarro Pérez, Daniela Josefina; Moreno Díaz, Juan Carlos; Simeone Barrientos, Pedro Alejandro (My University, 2022)
Due to the worldwide COVID-19 pandemic, Chilean universities were forced to transition from face-to-face classes to online instruction. In response, the Department of Chemical Engineering (DIQ) at the University of Magallanes sought alternative strategies for remote teaching. This article reports on their experience of delivering technical process simulation skills to their final-year undergraduate chemical engineering students. Due to difficulties connecting with the commercial software Aspen HYSYS, which was housed at the university, the department turned to the open-source software, DWSIM, as an alternative. The material content was adapted, and video tutorials were created to meet learning objectives. The software was taught in a new module within the Project Engineering course to develop the skills needed forstudents to design and simulate a chemical plant. Positive feedback and constructive criticism were received from the students through anonymous surveys and discussion forums. In response, DIQ launched its YouTube channel, DIQ_DWSIM, which has had a positive impact on Spanish-speaking individuals seeking to learn DWSIM. Additionally, two universities have used the channel as support material for their process simulation courses. A second survey of the YouTube audience has further solidified the value of this open online educational resource for higher education learning.
Enseñanza remota de emergencia en simulación de procesos con DWSIM: un caso estudio DIQ-UMAG, Patagonia Chilena
Keywords: DWSIM; Process simulation; COVID-19; Remote emergency teaching; YouTube channel